The birds of Indonesia. Kukila checklist no. 1. Additions, corrections and notes - Andrew, Paul (KUKILA, 1992)
This is the first update of the Kukila Checklist of the birds of Indonesia. Further updates will be published when errors, omissions and new distributional records are reported. Contributors to this update are S. van Balen, K.D. Bishop, S. Frazier, D.A. Holmes, J. Hornbuckle and I.A.W. McAllen. Published papers on taxonomic or nomenclatural points will also be noted when affecting a name or species-limits of a species recorded in Indonesia. This supplement is organized under three headings: Distribution, Classification and Miscellaneous Notes. However, the most unfortunate omission in the Checklist is in the Acknowledgements, where Professor Somadikarta should have been acknowledged, both as an editor of Kukila and for taxonomic advice.